Conceptualizations of "Rural": Challenges and Implications for Nursing Research - Frances E. Racher; Ardene Robinson Vollman; Robert C. Annis (Rural Nurse Organization; Binghamton University, 2004)
To identify the nature of the health of rural people and work towards sustaining, supporting, and improving that health, nurses must understand not only differences between rural and urban, but also differences within and among rural people. Nurses must understand the implications of defining "rural" in different ways and choose appropriate definitions based upon the foci of their research. In this paper, we discuss variations in the conceptualization of "rural," by examining descriptions, dichotomies, typologies and indices. Comprehensive understanding of these conceptualizations will inform nurses in conducting and using rural health research. This knowledge will extend their capacity to identify rural health research questions, to conduct research as insiders living in rural communities, and to use rural health research in providing care and planning programs.